Raising awareness of medical physics: The view of international atomic energy agency (IAEA). (September 2016) - Delis, H.; Poli, G.L.; Healy, B.; Christaki, K.; Loreti, G.; Meghzifene, A.
Abstract : The International Basic Safety Standards, published in 2014, recognizes the need for multidisciplinary approach to ensure Quality and Safety in Radiation Medicine. Specifically regarding the Medical Physics support, it is highlighted that corresponding requirements for calibration, dosimetry and quality assurance, including the acceptance and commissioning of medical radiological equipment, are fulfilled by or under the supervision of a medical physicist. The IAEA has been working to increase awareness on the need of comprehensive quality systems and accurate dosimetry practices in radiation medicine; these elements require the involvement of highly competent professionals, such as the medical physicists. Although the role of medical physicists in Radiation Therapy was been relatively well established for many years, corresponding involvement of medical physicists in imaging is still very weak, almost throughout the world. Historically, this can be partially justified by the large number of diagnostic departments and the perception of low complexity and doses in the field of medical imaging. However, the last few years, (i) the importance of accurate diagnosis to the patient management, (ii) the increasing complexity of diagnostic equipment and procedures, and (iii) the possibility of relatively high doses resulted from imaging procedures, have led to an increasing demand for medical physics support also in medical imaging. Supporting the Member States to establish medical physics capacities, the IAEA develops guidelines to harmonize the roles and the education and training requirements of medical physicist. In addition provides structured training to medical physics professionals, through individual fellowships, national, regional and interregional courses and workshops.